Every thing will be fine [videorecording (DVD)] - Franco, James, 1978-; Gainsbourg, Charlotte, 1971-; Croze, Marie-Josée, 1970-; McAdams, Rachel, 1978- (IFC Films, 2016)
A drama that charts the emotional odyssey of a struggling novelist whose life is turned upside down one wintry night following a fatal car accident. The incident sets him on a soul searching, decades long journey towards redemption, a quest that profoundly touches the lives of both his girlfriend and the accident victim's mother.